Perlindungan Hukum terhadap Istri atas Penelantaran Nafkah: Integrasi Pendekatan Fikih dan Hukum Positif Indonesia - Agus Jatnika; Mumu Fahmudin; Abdul Kodir Alhamdani (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
Maintenance neglect is a fundamental marital violation and a primary factor in high divorce rates. Currently, normative clashes exist between the classical fiqh approach in the Compilation of Islamic Law, such as the nusyuz concept, and the absolute penal regime in the Elimination of Domestic Violence Act. Furthermore, wives forced to file for divorce lawsuits often face post-divorce financial injustice. This normative research aims to analyze the integration of fiqh and Indonesian positive law to provide comprehensive legal protection for wives. Utilizing statutory and conceptual approaches based on Maqashid al-Shari'ah, the findings highlight the urgency for a gender-neutral reconstruction of nusyuz that includes the husband's nusyuz. Criminal proceedings for economic neglect under the Domestic Violence Act must also be synergized with a restorative justice approach. In the courts, protection can be optimized through the application of judges’ ex officio rights based on Supreme Court Regulation No. 3 of 2017 to secure post-divorce maintenance. The implication of this research demands national regulatory harmonization and the reformulation of court executory instruments to ensure the fulfillment of victims’ rights.